Just Add Milk: A Productivity Analysis of the Revolutionary Changes in Nineteenth Century Danish Dairying - Markus Lampe; Paul Sharp (European Historical Economics Society (EHES), 2014)
The late nineteenth century Danish agricultural revolution saw the modernization and growth of the dairy industry. Denmark rapidly caught up with the leading economies, and Danish dairying led the world in terms of productivity. Uniquely in a world perspective, high quality micro-level data exist documenting this episode. These allow the use of the tool of modern agricultural economists, stochastic frontier analysis, to estimate production functions for milk and thus find the determinants of these productivity and efficiency advances. We identify the contribution of modernization through specific new technologies and practices.
Keywords: L2; N5; O3; Q1; 330; Dairies; Denmark; development; Stochastic Frontier Analysis